Marketing Mix Strategy Remile - Hilda Yunita Wono; Reynaldo Raffael; Imanuel Deny Krisna Aji (Balai Pengembangan SDM dan Penelitian Komunikasi dan Informatika (BPSDMP Kominfo) Banjarmasin, 2021)
Craft is one of the oldest cultures in the world. In this modern era, the craft has become one of the export engines in Indonesia, especially in the Indonesian creative economy subsector and with this the craft has become the third largest contributor to gross domestic product (GDP). This has become one of the supporting factors that led to the emergence of new ventures or new businesses in East Java engaged in the craft industry. Remile is a new venture business engaged in the field of crafts, namely leather crafts, based in Surabaya. In late 2017, the Remile company began to create and implement a marketing plan which ultimately led to significant sales. This research was conducted with the aim of knowing Remile's marketing plan in the form of a marketing mix, which was created and used to drive sales Remile products significantly with descriptive methods that use data collection techniques in the form of in-depth interviews and structured interviews. Based on the result of the interviews, Remile make several stages or sequences in its making of their marketing mix starting with the creation of a marketing plan to marketing mix that aims to maximize and provide effectiveness Remile in carrying out marketing.